2018
DOI: 10.1681/asn.2017121278
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor 21 Is Required for Branching Morphogenesis and Regulates the Gdnf-Axis in Kidney Development

Abstract: Background The mammalian kidney develops through reciprocal inductive signals between the metanephric mesenchyme and ureteric bud. Transcription factor 21 (Tcf21) is highly expressed in the metanephric mesenchyme, including Six2-expressing cap mesenchyme and Foxd1-expressing stromal mesenchyme. Tcf21 knockout mice die in the perinatal period from severe renal hypodysplasia. In humans, Tcf21 mRNA levels are reduced in renal tissue from human fetuses with renal dysplasia. The molecular mechanisms underlying thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 57 publications
6
23
0
Order By: Relevance
“…During glomerular maturation, the Wilms tumor suppressor gene ( WT1 ) is expressed in the metanephrogenic mesenchyme, which positively regulates Tcf21 , inducing podocyte differentiation ( 36 , 37 ). TCF21 may regulate differentiation through the inhibition of cell cycle arrest-promoting factors in the HEK293 cell line, such as p21, which promotes the expansion of undifferentiated precursor cells and Gdnf-Ret-Wnt1 pathway activation required for mouse branching morphogenesis ( 25 , 38 ).…”
Section: Tcf21 In Kidney Developmentmentioning
confidence: 99%
“…During glomerular maturation, the Wilms tumor suppressor gene ( WT1 ) is expressed in the metanephrogenic mesenchyme, which positively regulates Tcf21 , inducing podocyte differentiation ( 36 , 37 ). TCF21 may regulate differentiation through the inhibition of cell cycle arrest-promoting factors in the HEK293 cell line, such as p21, which promotes the expansion of undifferentiated precursor cells and Gdnf-Ret-Wnt1 pathway activation required for mouse branching morphogenesis ( 25 , 38 ).…”
Section: Tcf21 In Kidney Developmentmentioning
confidence: 99%
“…Park and associates (22) studied lung cell populations that lineage-labeled for Tcf21, which is a specific marker of white adipose tissue and defines progenitor populations in the heart and kidney (2,8). Lineage labeling at embryonic day (E)11.5, shortly after outpouching of the laryngeo-tracheal groove, which heralds airway branching, identified both peribronchial and vascular smooth muscle cells.…”
mentioning
confidence: 99%
“…Ao et al [ 24 ] reported that TCF21 functions as a corepressor in the ERα signaling pathway and disrupts the growth of ERα-positive breast cancer cells. Ide et al [ 25 ] reported that TCF21 regulates kidney development by activation of the Gdnf-Ret-Wnt11 pathway, which is required for branching morphogenesis. These results, together with our findings, clearly demonstrate that TCF21 modulates multiple biological processes through different signaling pathways.…”
Section: Discussionmentioning
confidence: 99%